2010
DOI: 10.1186/1476-4598-9-78
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of eukaryotic translation initiation factor 4 gamma 1 correlates with tumor progression and poor prognosis in nasopharyngeal carcinoma

Abstract: BackgroundThe aim of the present study was to analyze the expression of eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) in nasopharyngeal carcinoma (NPC) and its correlation with clinicopathologic features, including patients' survival time.MethodsUsing real-time PCR, we detected the expression of EIF4G1 in normal nasopharyngeal tissues, immortalized nasopharyngeal epithelial cell lines NP69, NPC tissues and cell lines. EIF4G1 protein expression in NPC tissues was examined using immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 27 publications
7
35
0
Order By: Relevance
“…We chose to examine the oncogenic potential of EIF4G1, which regulates the initiation of translation of mRNAs encoding mitochondrial, cell survival, and cell-growth-associated genes in response to different stresses (Ramírez-Valle et al 2008, Silvera et al 2009). Overexpression of EIF4G1 was observed in breast cancer and nasopharyngeal carcinoma, and treatment with rapamycin mediated downregulation of the gene in breast cancer (Silvera et al 2009, Tu et al 2010. In two human MTC cell lines and a rat pheochromacytoma cell line, we found that ectopic expression of mutant EIF4G1 increases cell proliferation in a background of WT gene expression.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We chose to examine the oncogenic potential of EIF4G1, which regulates the initiation of translation of mRNAs encoding mitochondrial, cell survival, and cell-growth-associated genes in response to different stresses (Ramírez-Valle et al 2008, Silvera et al 2009). Overexpression of EIF4G1 was observed in breast cancer and nasopharyngeal carcinoma, and treatment with rapamycin mediated downregulation of the gene in breast cancer (Silvera et al 2009, Tu et al 2010. In two human MTC cell lines and a rat pheochromacytoma cell line, we found that ectopic expression of mutant EIF4G1 increases cell proliferation in a background of WT gene expression.…”
Section: Discussionmentioning
confidence: 79%
“…Among the 13 genes with either SNVs or copy number alterations, we further investigated the functional roles of EIF4G1 and GRAP in MTC and PCC cell lines because of their previously described association with malignancy (Feng et al 1996, Silvera et al 2009, Tu et al 2010, Patel et al 2012.…”
Section: Functional Analysis Of Eif4g1 and Grapmentioning
confidence: 99%
“…In nasopharyngeal cancers, Tu et al demonstrated that eIF4G1 mRNA and protein expression was significantly elevated in the tumour compared to nine surrounding tissue, where it positively correlated with TNM-staged tumour progression and reduced survival time [53]. Tu et al also highlighted that inhibiting expression of eIF4G1 by shRNA resulted in the suppression of cell migration/invasion, proliferation/cell cycle progression, colony formation and xenograft tumour growth in vivo [53].…”
Section: Translational Regulation Of the β6 Gene By Eukaryotic Initiamentioning
confidence: 97%
“…Collectively, this suggests that significant upregulation of eIF4G1 with β6 expression may facilitate an altered translational programme, influencing the expression of downstream proteins. eIFG1 is also an effector of mTOR signalling activity (following its phosphorylation) and has been observed to be elevated in breast [52], nasopharyngeal [53] and squamous cell lung cancers [54] where it is associated with metastatic progression and poor patient survival. Badura et al identified that elevated eIF4G1 expression in breast cancer selectively increased the translation of mRNAs involved in promoting cell survival, the prevention of apoptosis and autophagy following genotoxic DNA damage [48].…”
Section: Translational Regulation Of the β6 Gene By Eukaryotic Initiamentioning
confidence: 99%
“…It has been detected that NPC patients with higher eukaryotic translation initiation factor 4 g1 (EIF4G1) expression had shorter overall survival. Using shRNA to knock down the expression of EIF4G1 not only markedly inhibited cell cycle progression, proliferation, migration, invasion and colony formation, but also dramatically suppressed in vivo xenograft tumor growth [19].…”
Section: Prognostic or Metastasis Biomarkersmentioning
confidence: 99%